2015
DOI: 10.1021/nl503779e
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Patterns of Quantum Dots Formed by Electrohydrodynamic Jet Printing for Light-Emitting Diodes

Abstract: Here we demonstrate materials and operating conditions that allow for high-resolution printing of layers of quantum dots (QDs) with precise control over thickness and submicron lateral resolution and capabilities for use as active layers of QD light-emitting diodes (LEDs). The shapes and thicknesses of the QD patterns exhibit systematic dependence on the dimensions of the printing nozzle and the ink composition in ways that allow nearly arbitrary, systematic control when exploited in a fully automated printing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
298
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(301 citation statements)
references
References 56 publications
0
298
0
3
Order By: Relevance
“…4g, h). 104 E-jet printing uses the electric field to eject the QD ink with a narrow width, and the resulting QD pattern shows uniform line thicknesses. Using this printing method, red and green QD pixels are formed with a resolution up to that of the commercial display.…”
Section: Patterning Technology Of Qds For Full-color Displaysmentioning
confidence: 99%
“…4g, h). 104 E-jet printing uses the electric field to eject the QD ink with a narrow width, and the resulting QD pattern shows uniform line thicknesses. Using this printing method, red and green QD pixels are formed with a resolution up to that of the commercial display.…”
Section: Patterning Technology Of Qds For Full-color Displaysmentioning
confidence: 99%
“…Optical microscope imaging indicates that the lines are *35 microns in width. Recent studies have also shown that e-jet printing can be used to pattern QDs for LEDs (Kim et al 2015). …”
Section: Printingmentioning
confidence: 99%
“…In the case of a strain sensor, when wireless transmission functions, including power and data transfer, are not incorporated, a hard wire connection is required with an external measuring device, which degrades the durability of the device and significantly limits the user's activity when worn. Recent work demonstrates various wireless chemical and biological sensor systems with Bluetooth 23,24 and near-field-communication (NFC) [25][26][27] capabilities, the latter of which can also be operated in a battery-free mode via power harvesting. However, previously reported liquid metal-based antennas tend to be unsuitable for skin-attachable applications in terms of size or thickness, mostly because of limitations in the injection method.…”
Section: Introductionmentioning
confidence: 99%